Good Parenting as A Solution to Prevent Children as Sexual Abuse: Case Study of Solution by The Service of Women’s Empowerment, Child Protection, Population Control and Family Planning, Tegal, Central Java - Aulia, Rahma; Yulianti, Enny (Ijtimā iyya Journal of Muslim Society Research, 2023)
This study aims to determine the relationship between parenting patterns and sexual abuse behavior in children in Tegal Regency, Central Java Province. To answer these problems, this paper uses a case approach method, as well as a conceptual approach. The results of this study can be concluded that parenting is a capital for children to reach the maturity process. Family is the first social environment that individuals encounter since they were born into the world. The first family environment is the father, mother and the individual himself. The relationship between the individual and his parents is a reciprocal relationship where there is interaction in it. So it is proper as a good parent to be able to apply parenting that will form a good child's personality starting from an early age. The influence of increasingly sophisticated digital technology also has an impact on sexual violence against children, so parents are also required to monitor addictive behavior related to digital technology and prevent negative impacts due to long-term use of digital devices. Suggestions for parents to need to determine the right parenting pattern and improve the quality and quantity of communication with children and have a good trusting relationship so that the problem of sexual abuse behavior in children can be overcome and avoided.